FEATURESF CRISIS INTERACTIONS IN CONTEMPORARY SOCIAL SPACE - Сідоркіна, О. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
This article discusses the processes and interactions in the structure of the social, historical and spiritual space of Ukrainian society in terms of destructive phenomena are determined by their features.